Surgery for primary CNS lymphoma? Challenging a paradigm - Weller, Michael (Oxford University Press, 2012)
The standard of care for primary central nervous system lymphoma (PCNSL) is systemic chemotherapy with or without whole brain radiotherapy or intrathecal chemotherapy. In contrast to treatment for other brain tumors, efforts at resection are discouraged. This is a secondary analysis of the German PCNSL Study Group–1 trial, a large randomized phase III study comprising 526 patients with PCNSL. Progression-free survival (hazard ratio [HR]: 1.39; 95% confidence interval [CI]: 1.10–1.74; P = .005) and overall survival (HR: 1.33; 95% CI: 1.04–1.70; P = .024) were significantly shorter in biopsied patients compared with patients with subtotal or gross total resections. This difference in outcome was not due to age or Karnofsky performance status (KPS). When controlled for the number of lesions, the HR of biopsy versus subtotal or gross total resection remained unchanged for progression-free survival (HR = 1.37; P = .009) but was smaller for overall survival (HR = 1.27; P = .085). This analysis of the largest PCNSL trial ever performed challenges the traditional view that the extent of resection has no prognostic impact on this disease. Therefore, we propose to reconsider the statement that efforts at resection should be discouraged, at least if resection seems safe, as is often the case in treatment of single PCNSL lesions.